Early Growth of Chrysanthenum Explants Due to Various Concentration of Coconut Water During In Vitro Propagation - Ifayanti Ridwan*; Yunus Musa; Novaty E. Dungga; Katriani Mantja; Arfina Sukmawati Arifin; G. Gusmiaty; Idarni Tenri Pada Badwi; Muh. Farid BDR; Rahmawati S. (Universitas Sembilanbelas November Kolaka, 2023)
A study aimed to determine the effect of coconut water on the growth of Chrysanthemum explants was conducted. The study was carried out in the form of factorial experiments at Tissue Culture Laboratory, Department of Agronomy, Faculty of Agriculture, Hasanuddin University from December 2022 to March 2023. Media used was Murashige and Skoog (MS) added with three dose of coconut water, 100, 200, and 300 ml, respectively. Plantlets of five varieties of Chrysanthemum, Pinka Pinky, White Bakardy, Maruta, Kineta, and Dera obtained from Tissue Culture Laboratory, Horticultural Plant Seed Center, Bonto-bonto District, Gowa Regency. The explants were planted in Murashige and Skoog (MS) media containing the coconut water according to the treatments. Each combination of treatment was repeated three times. Results show that addition of 100 ml coconut water into the MS media was the best dose for plantlets growth indicated by earliest shoot emergence (9.04 days) and plantlet formation (9.25 days), and highest average number of leaves (15.00 leaves). The coconut water treatment of 200 ml showed the highest average number of roots (14.67 roots). Variation in responses between varieties were observed.